EFFECTIVENESS OF EMPOWERMENT PROGRAM ON QUALITY OF LIFE AND SELF EFFICACY OF PATIENTS UNDERGOING HEMODIALYSIS TREATMENT - Mr. Saeedullah; Mr. Shahzad Bashir; Mr. Santosh Kumar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Chronic kidney disease prevalence is very high. Almost one out of ten people are involved globally. CKD causes a high burden on patients' physical and psychological health. Hemodialysis patients have various physical, emotional, and social health issues. Empowerment initiatives may facilitate behavioral improvements and general health. Objective: To evaluate the effectiveness of the empowerment program on quality of life, self-efficacy, and clinical indicators of patients undergoing hemodialysis treatment. Methodology: This was a single group pre-post quasi-experimental study. Study was conducted in three tertiary care hospitals on patients undergoing hemodialysis treatment. A total of sixty participants were selected. Patients having at least three months of dialysis were included. Quality of Life Satisfaction Index and Strategies Used by People to Promote Health were used to determine the study outcome. Quality of life and self-efficacy were measured before and after eight sessions of the empowerment program interventions. Results:  The study finding shows mean difference (Mean ± SD) in quality of life was found before (99.75±10.3) and after (132.35±5.4), and also in self-efficacy before (72.2±8.7) and after (110.95±7.8). There was a significant difference in the pre-and post-quality of life and self-efficacy with a p-value of